A modelling framework to optimize timing of haulout counts for estimating harbour seal (Phoca vitulina) abundance - Cronin, Michelle; Zuur, Alain F; Ingram, Simon N; Rogan, Emer (NAMMCO Scientific Publications, 2010)
The time of year and day, the state of the tide and prevailing environmental conditions significantly influence seal haulout behaviour. Understanding these effects is fundamentally important in deriving accurate estimates of harbour seal abundance from haulout data. We present a modelling approach to assess the influence of these variables on seals’ haulout behaviour and, by identifying the combination of covariates during which seal abundance is highest, predict the optimal time and conditions for future surveys. Count data of harbour seals at haulouts in southwest Ireland collected during 2003-2005 were included in mixed additive models together with environmental covariates, including season, time of day and weather conditions. The models show maximum abundance at haulout sites occurred during midday periods during August and in late afternoon/early evening during September. Accurate national and local population estimates are essential for the effective monitoring of the conservation status of the species and for the identification, management and monitoring of Special Areas of Conservation (SAC) in accordance with the EU Habitats Directive. Our model based approach provides a useful tool for optimising the timing of harbourseal surveys in Ireland and the modelling framework is useful for predicting optimal survey periods for other protected, endangered or significant species worldwide.
Keywords: harbour seals; haulout behaviour; surveys; abundance